Assessment of Biological and Environmental Phenology at a Landscape Level from 30 Years of Fixed-Date Repeat Photography in Northern Sweden - Christopher Andrews; Jan Dick; Christer Jonasson; Terry Callaghan (AMBIO, 2011)
A 30-year series (1978–2007) of photographic records were analysed to determine changes in lake ice cover, local (low elevation) and montane (high elevation) snow cover and phenological stages of mountain birch (Betula pubescens ssp. czerepanovii) at the Abisko Scientific Research Station, Sweden. In most cases, the photographic-derived data showed no significant difference in phenophase score from manually observed field records from the same period, demonstrating the accuracy and potential of using weekly repeat photography as a quicker, cheaper and more adaptable tool to remotely study phenology in both biological and physical systems. Overall, increases in ambient temperatures coupled with decreases in winter ice and snow cover, and earlier occurrence of birch foliage, signal a reduction in the length of winter, a shift towards earlier springs and an increase in the length of available growing season in the Swedish sub-arctic.